2017
DOI: 10.1007/s12603-016-0829-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure is associated with tea consumption: A cross-sectional study in a rural, elderly population of Jiangsu China

Abstract: Habitual tea consumption was found to be associated with lower values of components of BP and a reduced likelihood of having hypertension in older adults. Given the widespread consumption of tea throughout China and the world, together with the major cardiovascular disease risk, our findings have important implications for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…A cohort study in China suggested that tea consumption (mainly green tea) has benefits on hypertension, especially in participants over 60 years old who do not have hypertension or are taking antihypertensive drugs (Yin et al., ). A Japanese cohort analysis indicated that a higher amount of green tea consumption was consistently related to the decrease of CVD mortality risk, especially for the coronary heart disease among Japanese women.…”
Section: Tea Chemistrymentioning
confidence: 99%
“…A cohort study in China suggested that tea consumption (mainly green tea) has benefits on hypertension, especially in participants over 60 years old who do not have hypertension or are taking antihypertensive drugs (Yin et al., ). A Japanese cohort analysis indicated that a higher amount of green tea consumption was consistently related to the decrease of CVD mortality risk, especially for the coronary heart disease among Japanese women.…”
Section: Tea Chemistrymentioning
confidence: 99%
“…The results from the Observation of Cardiovascular Risk Factors in Luxembourg study showed that daily consumption of 100 mL of tea decreased the systolic blood pressure (SBP) by 0.6 mmHg and pulse pressure by 0.5 mmHg [38]. In another study, a cross-sectional study conducted on a rural elderly population in Jiangsu, China, found that tea consumption was significantly and inversely associated with diastolic blood pressure (DBP) (coefficient = −0.74, p = 0.003), and frequent tea drinking could reduce the risk of hypertension with OR 0.79 (95% CI: 0.65–0.95), p = 0.011 [39]. Moreover, in a longitudinal study conducted on 80,182 Chinese individuals (49 ± 12 years of age), regular tea drinking was found to inhibit the decrease of the serum high-density lipoprotein cholesterol (HDL-C) level in men aged 60 or older, which could reduce the risk of CVDs because a low concentration of HDL-C was suggested to be responsible for high risk of CVDs [40,41].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…When arterial stiffness increases, the cushioning function is impaired, leading to a higher SBP and lower DBP. Stiffening of the arterial walls is a very important determinant of the development of hypertension [33,34,35,36]. Therefore, improvement in arterial elasticity is another mechanism for prevention of hypertension.…”
Section: Tea Regulating Blood Pressure In Human Intervention Studiesmentioning
confidence: 99%
“…This suggests that regular tea consumption may have a favorable effect on blood pressure in older women. Recently, Yin et al conducted a cross-sectional study of blood pressure and tea consumption an elderly population in Jiangsu, China [35]. A total of 4579 older adults aged 60 years or older participated in this study.…”
Section: Tea Regulating Blood Pressure In Human Intervention Studiesmentioning
confidence: 99%